2015
DOI: 10.3389/fpls.2015.00038
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of reference genes for RT-qPCR in the desert moss Syntrichia caninervis in response to abiotic stress and desiccation/rehydration

Abstract: Syntrichia caninervis is the dominant bryophyte of the biological soil crusts found in the Gurbantunggut desert. The extreme desert environment is characterized by prolonged drought, temperature extremes, high radiation and frequent cycles of hydration and dehydration. S. caninervis is an ideal organism for the identification and characterization of genes related to abiotic stress tolerance. Reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) expression analysis is a powerful analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 72 publications
2
42
0
Order By: Relevance
“…α-TUB2 encoding a cytoskeleton structure protein62 and DnaJ encoding a cellular chaperone have the ability to repair heat-induced protein machinery damage6364. Our results are in agreement with several previous studies, which showed that α-TUB2 and DnaJ were established as the most stable reference genes in plants under abiotic stresses; for example, in Syntrichia caninervis under drought, salt, and heavy metal stresses65, Corchorus capsularis under drought stress10, Buchloe dactyloides under salt stress66 , and Platycladus orientalis under salt stress67. Normalization with multiple reference genes is an effective way to avoid erroneous data that may result from using a single reference gene68.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…α-TUB2 encoding a cytoskeleton structure protein62 and DnaJ encoding a cellular chaperone have the ability to repair heat-induced protein machinery damage6364. Our results are in agreement with several previous studies, which showed that α-TUB2 and DnaJ were established as the most stable reference genes in plants under abiotic stresses; for example, in Syntrichia caninervis under drought, salt, and heavy metal stresses65, Corchorus capsularis under drought stress10, Buchloe dactyloides under salt stress66 , and Platycladus orientalis under salt stress67. Normalization with multiple reference genes is an effective way to avoid erroneous data that may result from using a single reference gene68.…”
Section: Discussionsupporting
confidence: 92%
“…Four reference genes, DnaJ, α-TUB2, MUB , and ACT under drought stress, were needed for accurate normalization. Two reference genes were found to be sufficient to analyze the expression of target genes in sorghum62, jute10, and moss65.…”
Section: Discussionmentioning
confidence: 99%
“…grown under high light stress [61]. Similarly, a second study realized with Syntrichia caninervis under abiotic stress; the α-Tub gene was also found to be stable amongst 15 reference genes, and 18S was the less unstable one [41].…”
Section: Discussionmentioning
confidence: 87%
“…Gene coding for Act, 18S RNA, α-TUB, and β-TUB was used for the screening of the most stable gene in all experiment conditions as they are known to be classic plant reference gene candidates [41]. Quantification cycle (Cq) values were imported into the comprehensive web-based tool RefFinder (http://150.216.56.64/referencegene.php?type=reference), which integrates commonly used reference gene evaluation programs together, including geNorm, NormFinder, Bestkeeper, and the comparative delta Ct methods [41,42]. Results elaborated by RefFinder were confirmed by GeNorm, which is available on excel file [43].…”
Section: Primers Design and Validation Reference Gene Selectionmentioning
confidence: 99%
“…However, these traditional reference genes are not always stably expressed under different conditions (Xiao et al 2015. Even for the same plant, reference genes may show different stability patterns under different stresses (Li et al 2015, Xiao et al 2015. Therefore, it is necessary to establish suitable reference genes for each species and tested them under certain experimental conditions in order to ensure their stability (Li et al 2012, Zhao et al 2016, Acevedo et al 2017.…”
Section: Introductionmentioning
confidence: 99%